A Study Of Muslims’ Perceptions Of Zakat As A Tax Reduction In Malaysia And Indonesia - Aula Ahmad Hafidh Saiful Fikri; Sharifah Faigah Syed Alwi; Fuadah Johari; Maimun Sholeh; Eko Suprayitno; Ngadiyono (Macrothink Institute, United States, 2024)
Volume: 12 No :1 (page: 60-75)